The Global Role of Mawlana Muhammad Anwar Badakhshani in the Dissemination of Islamic Sciences and Knowledge - HAMIDI, Abdulbari (Integrated Journal for Research in Arts and Humanities, 2024)
This article aims to explain the intellectuals and elites of every era is essential for better utilizing their knowledge and experiences. Mawlana Muhammad Anwar Badakhshani, a contemporary scholar from Badakhshan Afghanistan, gained widespread recognition through his teaching, research, and extensive writings. He acquired Islamic sciences from renowned scholars in Afghanistan and Pakistan and trained thousands of capable students who contributed to society across the Islamic world. Mawlana Anwar's works exceed forty, with his translation and interpretation of the Holy Quran being among the most prominent. His proficiency in multiple languages, including Persian, Arabic, English, and Urdu, allowed him to author texts that were widely accessible. His scholarship spanned various fields, including Quranic exegesis, Hadith, jurisprudence, logic, philosophy, literature, and history. Mawlana Badakhshani's writings are distinguished by their simplicity, making complex subjects accessible to a broader audience. Notable works include “Tashil al-Mantiq” (Simplification of Logic) and “Tashil Usul al-Shashi” (Simplification of Usul al-Shashi). This article highlights the importance of recognizing and introducing Afghanistan's scholars, as understanding their contributions is crucial for shaping a brighter future. Mawlana Badakhshani’s life journey, marked by perseverance and dedication, serves as a testament to the heights of knowledge that can be achieved through relentless effort.